Optimizing Insurance Sales through Automated Lead Management - Rahul Deb Chakladar (North American Journal of Engineering Research, 2023)
This paper delves into the challenges of managing high lead volumes in the insurance industry and the benefits of implementing Sales Automation solutions. It explores how these solutions optimize lead management, enhance sales processes, and increase deal sizes through intelligent automation and data analysis. The paper also emphasizes the importance of targeted marketing strategies, AI and machine learning, data protection, and compliance. Additionally, it highlights the significance of key performance indicators (KPIs) in refining lead generation strategies for sustained growth.